Propriedade intelectual e suas implicações constitucionais: análise do perfil constitucional da propriedade intelectual e suas inter-relações com valores constitucionais e direitos fundamentais - Rocha, Afonso de Paula Pinheiro (2008)
The work looks for to offer a legal overview of the relations that the intellectual property have with several values and constitutional rights, trough research of specialized doctrines and jurisprudences, both national and international. It offers an introductory notion of intellectual property and the elements that link the related doctrines of this field of law. The main types of theories that justify the existence of intellectual property presented with their underlying ideologies and practical implications in the definition of the legal protection scope. It does an economic a analysis of intellectual goods. It provides the historical evolution of intellectual property protection in the doctrines of industrial property, copyright and author’s rights. Several cases are show to indicate the progressive expansion of intellectual property rights both in scope and duration. The work demonstrates the close relation of intellectual property and human rights, especially in the context of the economic, social and cultural rights. Regarding Brazilian law, it is shown the evolution of the constitutional treatment of intellectual property, as well as the idea of a social function for intellectual property. Finally, several issues that have intellectual property as an underlying theme are presented such as access to the health, food, education, culture and antitrust. The work presents as conclusion the necessity to rethink the balance that must be inherent to intellectual property, as a way to promote an effective cultural and technological development in a democratic and solidary manner.